Effect Of combining FK506 and neurotrophins on neurite branching and elongation. Issue 4 (28th December 2016) - Labroo, Pratima; Shea, Jill; Sant, Himanshu; Gale, Bruce; Agarwal, Jayant
ABSTRACT: Introduction: There is a clinical need to improve the outcomes of peripheral nerve regeneration and repair after injury. In addition to its immunosuppressive effects, FK506 (tacrolimus) has been shown to have neuroregenerative properties. To determine biologically relevant local FK506 and growth factor concentrations, we performed an in vitro bioassay using dorsal root ganglion (DRG) from chicken embryos. Methods: Neurite elongation and neurite branching were analyzed microscopically after addition of FK506, glial cell line‐derived neurotrophic factor (GDNF), and nerve growth factor (NGF), each alone and in combination. Results: FK506 induced modest neurite elongation (∼500–800 µm) without improving neurite branching significantly. The combination of FK506 with NGF, GDNF, or both, exerted a potentiating or competitive effect on neurite elongation (∼700–1100 µm) based on dosage and competitive effect on neurite branching (∼0.2–0.4). Conclusions: These results strongly suggest that the interaction of FK506 with GDNF and NGF mediates distinct enhancement of neurite growth. Muscle Nerve 55 : 570–581, 2017